Kube Smart Biz Pendampingan Usaha Cerdas untuk Optimalisasi Produk dan Pemasaran: Sosialisasi Kube untuk Optimalisasi Produk dan Pemasaran UMKM di Kelurahan Gunung Lengkuas - Kornelius Niko Endrawan; Rosa Febby Octavia Tampubolon; Grachiella Dian Malemukur; Arinda Amalia Putri; Adilla Niagara; Aina Puji Astuti; Asliyati Asliyati; Rahmad Ananda; Ferry Irmansyah; Rony Dramendran Manik; et al. (Jurnal Pengabdian Masyarakat, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in driving economic growth and community empowerment based on local potential. However, limitations in terms of capital, management and marketing remain major challenges faced by MSME players, especially in the processed food sector. This community service activity aims to increase the capacity of MSME players by strengthening product visual identity and utilising digital marketing. The implementation methods include delivering materials, practising packaging design and visual identity, and providing assistance in using social media as a marketing tool. Evaluation is carried out through the distribution of questionnaires and joint reflection to measure the level of understanding, the benefits of the activity, and the obstacles faced by participants. The results of the activity showed an increase in MSME actors’ understanding of the importance of attractive and consistent packaging design, as well as the use of social media as an effective and low-cost marketing strategy. This activity is expected to encourage the independence of MSME actors, increase product competitiveness, and support sustainable business development.